Strategies for Enhancing the Competitiveness of Leather Bag Industry - Syifa Fitriani; Nurrani Natasya Putri; Choirul Bariyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The leather industry in numerous countries, including Indonesia, continues to encounter significant challenges that impede its competitiveness in both domestic and international markets. Abekani Leather, a small and medium-sized enterprise (SME) operating within the leather industry in Yogyakarta, is one such entity striving to remain competitive against other players in the sector. Based on interviews conducted with the owner of Abekani Leather, it was revealed that annual sales from 2018 to 2023 have declined by approximately 10-15%. This downturn is primarily attributed to the increasing presence of competitors offering similar products within the leather industry. Based on the AHP weighting results using the Super Decision software, it can be concluded that the alternative strategy SO-4 (Utilizing social media for promotions in various media by utilizing community relationships) has the highest weight value of 0.54, meaning this strategy should be prioritized first to achieve Abekani's objectives.